Farmers’ perceptions of hydroclimatic variability and climate change: survey-based insights in Northern Benin, West Africa - Orou Moctar Ganni Mampo; Orou Moctar Ganni Mampo; Orou Moctar Ganni Mampo; Kossi François Guedje; Kossi François Guedje; Bruno Merz; Bruno Merz; Halissou Yarou; Elena Macdonald; Adéchina Eric Alamou; Adéchina Eric Alamou (Frontiers in Water)
Farmers in West Africa face increasing challenges from droughts and hydroclimatic variability, exacerbated by climate change. Understanding these changes and their drivers is crucial for developing effective adaptation strategies. This study investigates farming households in Northern Benin, assessing their knowledge of hydroclimatic variability and identifying the factors influencing their understanding. Using a questionnaire survey of 509 households across 96 villages in eight municipalities, we analysed both qualitative and quantitative data through statistical methods and machine learning methods. Results reveal that while 71% of farmers have a solid grasp of local hydroclimatic variability, significant gaps remain regarding its underlying causes; only 9% attributed temperature increases to global climate change. Older farmers (mean age: 55 years) and those with over 30 years of experience demonstrated higher knowledge than less experienced farmers. Conversely, formal education had little to no impact. These findings highlight the critical role of indigenous knowledge, accumulated through long-term environmental interaction, in shaping climate awareness. They underscore the need to integrate indigenous knowledge with formal education to improve the understanding of the drivers of these changes. Targeted investments in education, alongside leveraging the experiential knowledge of older farmers, can enhance climate resilience in vulnerable regions. These insights provide a novel perspective on how policymakers can bridge traditional wisdom and modern scientific approaches for more effective climate adaptation.